Kajian Rencana Produksi Alat Gali Muat dan Angkut dalam Pengoptimalan Kegiatan Penambangan Emas di PT DEF Kecamatan Simpenan, Kabupaten Sukabumi, Provinsi Jawa Barat - Muhammad Yusuf Samith; Zaenal; Indra Karna (Bandung Conference Series: Mining Engineering, 2022)
Abstract. PT DEF is a company engaged in mining with gold ore commodities located in Simpenan District, Sukabumi Regency, West Java Province. In mining activities, the use of tools in the form of digging, loading, and unloading equipment and transportation equipment. The type of equipment used is the Kobelco SK320 with a bucket capacity of 1.8 LCM as many as 2 units, while the conveyance is a Hino FM 260 JD type with a 20 LCM tailgate capacity of as many as 6 units. In the production target of 1,187,292 BCM/hour, the increase in production can be improved by following the standards of AASHTO (American Association of State Highway and Transportation Officials) and Ministerial Decree No. 1827/K/30/MEM/2018. AASHTO and Kepmen No.1827/K/30/MEM/2018. Supporting data for fuel is the geometry of the road, hours meter on the tool, the ratio of fuel and the value of the cost of the fuel produced as costs that must be incurred in mining activities using mechanical tools. In the results of the study, based on the specifications of the conveyance it has a width of 2,480 m so that in straight road conditions with 1 lane it gets 4,980 meters and in 2 lane conditions it gets 8,715 meters and the width of the bending road is 8.7 - 13.7 meters. For road slopes, the grade varies starting from 1.9% - 59.34% with a maximum standard grade of 12% so that 11 road segments are repaired. The actual superelevation condition starts from 13.91% - 68.97% based on the calculation of the minimum superelevation is 8% so that simulations are carried out on each superelevation segment. In terms of fuel consumption, the average loading and unloading equipment is 33.94 liters/month and in terms of fuel consumption for transportation equipment the average is 22.54 liters/month. for the fuel ratio of the digging equipment is 6.81 liters/month and the result of the calculation of the fuel cost of the digging equipment is Rp. 500,921,959 per month and the means of transportation is Rp. 712,937,371 per month. Abstrak. PT DEF merupakan perusahaan yang bergerak di bidang pertambangan dengan komoditas bijih emas yang terletak di Kecamatan Simpenan, Kabupaten Sukabumi, Provinsi Jawa Barat. Dalam penunjang kegiatan penambangan, penggunaan alat mekanis berupa alat gali muat dan alat angkut. Jenis alat muat yang digunakan yaitu adalah Kobelco SK320 dengan kapasitas bucket 1,8 LCM sebanyak 2 unit, sedangkan pada alat angkut berjenis Hino FM 260 JD dengan kapasitas bak truck 20 LCM sebanyak 6 unit. Dalam pencapaian target produksi sebesar 1.187,292 BCM/Jam, peningkatan produksi dapat diperbaiki dengan mengikuti standar AASHTO ( American Association of State Highway and Transportation Officials) dan juga Kepmen No.1827/K/30/MEM/2018. AASHTO dan Kepmen No.1827/K/30/MEM/2018. Serta data yang menunjang untuk bahan bakar yaitu pada geomerti jalan, hours meter pada alat, fuel ratio dan dihasilkan nilai fuel cost sebagai biaya yang harus dikeluarkan dalam kegiatan penambangan menggunakan alat mekanis. Pada hasil penelitian, berdasarkan spesifikasi alat angkut memiliki lebar sebesar 2,480 m sehingga pada kondisi jalan lurus dengan 1 jalur didapatkan 4,980 meter dan pada kondisi 2 jalur didapatkan 8.715 meter dan lebar jalan tikungan sebesar 8,7 - 13,7 meter. Untuk kemiringan jalan memiliki grade bervariasi dimulai dari 1,9% - 59,34% dengan standar grade maksimal sebesar 12% sehingga terdapat 11 segmen jalan yang diperbaiki. Kondisi superelevasi aktual dimulai dari 13,91% - 68,97% berdasarkan perhitungan superelevasi minimum adalah 8% sehingga dilakukan simulasi perbaikan pada setiap segmen superelevasi. Dalam konsumsi bahan bakar rata-rata alat gali muat ini sebesae 33,94 liter/bulan serta dalam konsumsi bahan bakar alat angkut rata-tara sebesar 22,54 liter/bulan. Untuk fuel ratio alat gali muat sebesar 6,81 liter/bulan dan hasil perhitungan fuel cost alat gali muat sebesar Rp 500.921,959 per bulan dan pada alat angkut sebesar Rp 712.937,371 per bulan.